Gallbladder metastasis from occult lobular breast carcinoma: A case report - Dorić Mirsad; Čamdžić Nina; Durmišević Dževad; Babić Mirsad; Salčin Edina Lazović; Kuskunović-Vlahovljak Suada (Acta Marisiensis - Seria Medica, 2023)
Introduction: Bones, lungs, brain and liver are the most common metastatic sites of breast carcinoma, although invasive lobular carcinoma can give metastases to less common sites, such as the gastrointestinal tract and the female genital tract.